1997
DOI: 10.1097/00006123-199707000-00036
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Changes of Intraparenchymal Arterioles after Experimental Subarachnoid Hemorrhage in Dogs

Abstract: These results suggest that constriction of intraparenchymal arterioles occurs after SAH and may contribute to delayed cerebral ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
71
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 24 publications
4
71
0
Order By: Relevance
“…This hypothesis was proven experimentally in rats by showing that subarachnoid arterioles indeed constrict by B40% in the early phase, i.e., 5 minutes to 2 hours after SAH in vivo (Sun et al, 2009). Vasoconstriction also seems to affect intraparenchymal microvessels as soon as 10 minutes after SAH, as demonstrated by collagen IV and endothelial barrier antigen immunohistochemistry on fixed rat tissue (Sehba et al, 2007) and may last up to 7 days as shown using a casting technique in dogs (Ohkuma et al, 1997). That the observed changes at the level of the microcirculation are not an experimental artifact, but may indeed contribute to the post hemorrhagic pathophysiology of SAH in humans, were demonstrated by a study performed in our department which visualized the cerebral microcirculation in SAH patients during aneurysm clipping during the first 3 days after the initial bleed, i.e., at time points where macrovasospasm was not present (Uhl et al, 2003).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This hypothesis was proven experimentally in rats by showing that subarachnoid arterioles indeed constrict by B40% in the early phase, i.e., 5 minutes to 2 hours after SAH in vivo (Sun et al, 2009). Vasoconstriction also seems to affect intraparenchymal microvessels as soon as 10 minutes after SAH, as demonstrated by collagen IV and endothelial barrier antigen immunohistochemistry on fixed rat tissue (Sehba et al, 2007) and may last up to 7 days as shown using a casting technique in dogs (Ohkuma et al, 1997). That the observed changes at the level of the microcirculation are not an experimental artifact, but may indeed contribute to the post hemorrhagic pathophysiology of SAH in humans, were demonstrated by a study performed in our department which visualized the cerebral microcirculation in SAH patients during aneurysm clipping during the first 3 days after the initial bleed, i.e., at time points where macrovasospasm was not present (Uhl et al, 2003).…”
Section: Discussionmentioning
confidence: 92%
“…Another technical advantage of the current study is that it is one of the few to use intravital videomicroscopy for the direct visualization of the post hemorrhagic cerebral microcirculation in vivo (Ishikawa et al, 2009;Sun et al, 2009). In comparison with previous studies which described post hemorrhagic microvasospasm ex vivo by histology on fixed tissue or by casting techniques (Ohkuma et al, 1997;Sehba et al, 2007), the current study using in-vivo microscopy has the intrinsic advantages of studying vessels in the living brain, to be able to study the whole vascular tree of the MCA, to observe dynamic changes, e.g., thrombus formation, and to uncover dynamic interactions, e.g., vasoconstriction and microthrombosis. Finally, the current study was performed in a recently improved mouse SAH model (Feiler et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent histological study revealed that intraparenchymal small arteries or arterioles show luminal narrowing rather than dilation during cerebral vasospasm after experimental SAH. 5) Thus, although whether the peripheral arterioles are dilated or constricted at vasospasm remains unclear, disturbance of the intracerebral microcirculatory system may be involved in cerebral ischemia due to vasospasm. Microcirculatory changes manifesting as prolonged peripheral cerebral circulation time are thought to be involved in cerebral ischemia during cerebral vasospasm, 5) and the reduction in regional cerebral blood flow was significantly correlated with prolonged peripheral cerebral circulation time in our patients with angiographic vasospasm.…”
Section: Discussionmentioning
confidence: 99%
“…Even deterioration due to ischemia has been attributed to causes other than angiographic vasospasm; these include microvascular vasospasm, thromboembolism, and delayed neuronal apoptosis triggered by global ischemia occurring at the time of SAH. 38,39,49,52 Here we use the term delayed cerebral ischemia to mean ischemia from angiographic vasospasm.…”
Section: Definitions Of Terminologymentioning
confidence: 99%